Can the environmental impact of pig systems be reduced by utilising co-products as feed?. (1st March 2016) - Mackenzie, S.G.; Leinonen, I.; Ferguson, N.; Kyriazakis, I.
Abstract: The implications of using co-products from the supply chains of human food and biofuels in pig diets for the environmental impacts of Canadian pig systems were examined using Life Cycle Assessment. The functional unit was 1 kg expected carcass weight (ECW) and environmental impacts were calculated as: Acidification Potential (AP), Eutrophication Potential (EP), Global Warming Potential (GWP), Nonrenewable Energy Use (NRE) and Nonrenewable Resource Use (NRRU). Maximum inclusion limits which would not negatively affect animal performance were defined for: meat meal (55), bakery meal (87), corn DDGS (261) and wheat shorts (291) (numbers in brackets represent average across all feeding phases in g/kg as fed). Nutritionally equivalent grower/finisher (G/F) diets containing maximum inclusions of these co-products were formulated individually. These diets were compared to a simple control diet based on corn and soya meal using 1000 parallel Monte-Carlo simulations. The maximum inclusion of meat meal reduced NRRU and NRE per kg ECW by 9% and 8% compared to the control (P < 0.001), EP and AP increased by 10% and 7% (P < 0.001), with no significant change in GWP. Maximum inclusion of bakery meal was found to reduce all environmental impacts for all categories modelled by <5% (P < 0.001). Maximum inclusion of corn DDGS in the G/F diets resulted in relatively large increases in NRRU (56%), NRE (48%) and GWP (16%) (all P < 0.001). The maximum corn DDGS diet caused a mean reduction of <1% in AP (P = 0.01) and did not significantly alter EP. Maximum inclusion of wheat shorts reduced GWP, NRE and NRRE by >10% (P < 0.001) but did not significantly alter EP or AP. The environmental impact implications for pig farming systems of high inclusion levels of co-products in G/F diets formulated for economic goals (i.e. least cost per kg live weight gain), were also modelled for the first time. Four further G/F diets were formulated on a least cost basis at 100%, 97.5%, 95% and 92.5% of the energy density required for maximum feed efficiency. Minimum nutrient to net energy ratios were defined in the formulation rules to ensure the first limiting resource of all diets for growth was energy. The least energy dense diet contained the highest level of co-products (294 g/kg as fed) and the most energy dense diet contained the least (108 g/kg as fed). The least energy dense diet reduced NRE and NRRU by 9% (P < 0.001) and GWP by 4% (P = 0.018) when compared to the diet designed for maximum feed efficiency, but increased AP and EP by <1% (P < 0.001). The other two intermediate levels of energy density followed the same pattern but the effects were not linear. The increased inclusion of co-products in G/F diets formulated for economic goals can produce environmental impact reductions for some environmental impact categories in pig farming systems. Highlights: We model the environmental impacts of including co-products in pig diets using LCA. The four co products tested were meat meal, bakery meal, corn DDGS and wheat shorts. Wheat shorts and bakery meal reduced environmental impacts in equivalent diets. Less energy dense diets with increased co-products reduced Global Warming Potential. Less energy dense diets increased Acidification and Eutrophication Potential.